Detection of Staphylococcal Species Diversity within Human Skin Microbiome Using a Simple PCR-SSCP Technique (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Objective. The aim of this study was to detect the diversity of Staphylococcus species of a healthy human skin using a simple techniquevPCR-SSCP.Methods: Blood samples, saliva, and skin swaps samples were collected from 50 persons from Hilla City  - Iraq. The genomic DNA was extracted from these samples using the Bacteria Genomic DNA Kit. The concentrations and purity of DNA extract estimated by NanoDrop spectrophotometer. Polymerase chain reaction – single-strand conformational polymorphism (PCR–SSCP) technique was performed to detect the diversity between Staphylococcal species in the human skin microbiome using a specific primer of the 16SrRNA gene.Results: The PCR results, indicated that the Staphylococcal species were found within the ski community, but it's not infected blood and mouth of test healthy individuals. SSCP-heteroduplex patterns of PCR products appeared the presence Staphylococcal species diversity within skin microbiome of test healthy individuals.Conclusion: In spite of the PCR-SSCP, heteroduplex method was simple and cheap and appeared the diversity betweenvStaphylococcalspeciesvin the human skin microbiome, but it's not diagnosed the bacterial strains. So these results required to confirm by DNAvsequencingvtechnique.